Constructivist Theory: Learning to Ride a Motorcycle The Motorcycle Safety Foundation Basic RiderCourse® - Debra Finlayson (Adult Education Research Conference, 2010)
Designed as an experiential learning opportunity beginning with low learner involvement progressing to high involvement task mastery; a primary goal of the MSF Basic RiderCourse® provides an introduction to the fundamentals of safe and responsible motorcycling. Adult and contemporary educational theories and practices in brain-based, accelerated learning principles, motor skill learning and development, along with solid learner-centered instructional techniques present a low risk, positive learning environment. Participants in this session will have an opportunity to review examples of the course materials and discuss the many areas where constructivist orientation to learning applies in practice.